1987
DOI: 10.1148/radiology.165.2.3659350
|View full text |Cite
|
Sign up to set email alerts
|

Nonpalpable breast lesions: accuracy of prebiopsy mammographic diagnosis.

Abstract: Mammograms of 220 patients who underwent spot localization for removal of nonpalpable breast lesions were reviewed for accuracy of interpretation. Results of subsequent biopsy indicated malignancy in 77 cases. The interpretations of mammograms obtained before biopsy were incorrect in 71 cases (27 false-negative and 44 false-positive studies). Among the false-negative cases, 70% of the abnormalities were determined histologically to be noninfiltrative cancers. An aggressive screening program with preoperative l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
6

Year Published

1993
1993
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(14 citation statements)
references
References 0 publications
0
8
0
6
Order By: Relevance
“…It is reported that usually less than 30% of all breast biopsies actually show a malignant pathology. [3][4][5][6][7] The high number of unnecessary breast biopsies causes major mental and physical discomfort for the patients as well as unnecessary expenses spent for examinations. Therefore, computer-aided diagnosis ͑CADx͒ systems have been proposed in the past years with the aim to support radiologists in the discrimination of benign and malignant mammographic lesions and to increase the positive predictive value ͑PPV͒ of mammogram interpretation.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that usually less than 30% of all breast biopsies actually show a malignant pathology. [3][4][5][6][7] The high number of unnecessary breast biopsies causes major mental and physical discomfort for the patients as well as unnecessary expenses spent for examinations. Therefore, computer-aided diagnosis ͑CADx͒ systems have been proposed in the past years with the aim to support radiologists in the discrimination of benign and malignant mammographic lesions and to increase the positive predictive value ͑PPV͒ of mammogram interpretation.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the positive biopsy rate for nonpalpable breast lesions as well as for nonpalpable breast masses is between 15%-30%. [1][2][3][4] This means that 70%-85% of breast biopsies are performed for benign lesions. In order to reduce patient anxiety and morbidity, as well as to decrease health care costs, it is desirable to reduce the number of benign biopsies without missing malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…In three studies, it was found that only 20%-30% of mammographically suspicious nonpalpable breast masses that underwent biopsy were malignant. [1][2][3] In order to reduce costs and patient discomfort, it is important to reduce the number of benign biopsies without missing any malignant masses. Computer-aided diagnosis has the potential to assist the radiologists in the characterization of mammographic masses.…”
Section: Introductionmentioning
confidence: 99%